Rural capitalists in Asia : a comparative analysis on India, Indonesia, and Malaysia - Rutten, Mario (Nordic Institute of Asian Studies monograph series, 2003)
This is a comparative study of small capitalists and rural industrialists in three Asian countries. Studies on the entrepreneurial class in South Asia tend to focus on the structural aspects of entrepreneurial behaviour, while studies on this class in Southeast Asia tend to focus on cultural aspects of their behaviour. In fact, this book points to striking similarities between Indian, overseas Chinese and Muslim businessmen in Asia, similarities usually hidden under variations in analytical approaches. Although this study emphasizes similarities within Asia, it does not support the view of a s.